A conceptual model of Open Access Institutional Repository in Indonesia academic libraries. Issue 1 (12th January 2015) - Farida, Ida; Tjakraatmadja, Jann Hidajat; Firman, Aries; Basuki, Sulistyo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to attempt to build a conceptual model of Open Access Institutional Repositories (OAIR) in Indonesia academic libraries, viewed from knowledge management (KM) perspective. Design/methodology/approach – Literature-based conceptual analysis of previous studies related to open access, institutional repositories viewed from KM perpective. Findings – The conceptual model of OAIR emphasizes three variables – people collaboration, process, and technology functions. These variables, with their many elements, are integrated together in order to help the university or Higher Education (HE) institution in capturing its own scholarship produced as a whole. Besides, that integration aims at facilitating knowledge sharing so as to enrich knowledge content and to enhance global access. A process chart of OAIR based on the conceptual model is built to illustrate knowledge content recruitment in Indonesia academic libraries. Research limitations/implications – The conceptual model proposed in this paper is not yet formally tested. It needs more research to understand the Indonesian context of OAIR to build a more accurate model, based on the experiences in developing and implementing OAIR in Indonesia HE institutions. Originality/value – Many academic libraries in Indonesia develop OAIR to increase the visibility of the scholarship of the parent HE institution. It is significant to view the practice of OAIR in academic library from the KM perspective. KM implementation is almost unheard of in Indonesia universities. However, The OAIR phenomenon in Indonesia academic libraries can be viewed as a KM initiative.